The co-construction and emotion management of hope within psychosis services - Brown, Patrick; Scrivener, Amanda; Calnan, Michael (Frontiers in Sociology, 2024)
There is a growing acknowledgement of the salience of hope for mental health service-users, in influencing care outcomes and recovery. Understandings of the processes through which hopes are co-constructed, alongside specific conceptualisations of experiences of hoping, remain limited however. This qualitative study explored how a range of stakeholders experienced and dealt with uncertainty within three purposively selected psychosis services in southern England. In this article we focus particularly on the co-construction of hope within participants’ narratives and how this emotion work shaped experiences of hoping. In-depth interviews (n=23) with service-users, professionals, managers and other stakeholders were analysed following a phenomenological approach. Hope was spontaneously identified by participants as a fundamental mechanism through which service-users and professionals managed uncertainty when vulnerable. Professionals were influential in shaping users’ hopes, both intentionally and unwittingly, while some professionals also referred to managing their own hopes and those of colleagues. Such management of expectations and emotions enabled motivation and coping amidst uncertainty, for users and professionals, but also entailed difficulties where hope was undermined, exaggerated, or involved tensions between desires and expectations. Whereas hope is usually reflected in the caring studies literature as distinctly positive, our findings point to a more ambivalent understanding of hope, as reflected in the accounts of both service-users and professionals where elevated hopes were described as unrealistic and harmful, to the well-being of professionals as well as of service-users. It is concluded that a greater awareness within care contexts of how hopes are co-constructed by professionals and service-users, explicitly and implicitly, can assist in improving health care and healthcare outcomes.